Isolation Performance Improvement Using Defected Ground Structure In RF Switch - Abdul Hadi, Mohammad Hairi (2016)
The potential application of Defected Ground Structure (DGS) for isolation improvement of RF switch was presented in this thesis. The discrete PIN diode was used as switching element in the RF switch design and the PI diode relatively had a low isolation problem. Mathematical modeling was determined to model the equivalent circuit of the PIN diode with DGS. DGS can be modeled as a parallel connection of capacitor and inductor. Parameter study was applied to understand the relationship between inductance and capacitance of DGS and its dimension where the etched areas and the gap width under the DGS ground plane were strongly correlated with the inductance and capacitance of the DGS. Five pairs of inductance and capacitance values of DGS were varied to obtain resonant frequency at 4.0 GHz. Isolation fo1mulas was derived in S2 l parameter using transmission ABCD matrix. It can be seen that the resonant frequency of the discrete PIN diode with DGS was shifted to higher frequency during ON state and was shifted to lower frequency during OFF state. Isolation response of the equivalent circuit of PIN diode with DGS was analyzed at desired operating frequency of 1.5 GHz. The isolation improvement was achieved where PIN diode isolation was improved from -1 0. l dB to -35 dB at 1.5 GHz when DGS was employed. Based on the mathematical mode ling, Electromagnetic (EM) simulation was performed where commercialized NXP Semiconductor PIN diode model was applied to integrate with the square shaped DGS and circle shaped DGS. Both DGS types were designed at 4.0 GHz with different dimension layouts and the best attenuation of -22.5 dB and -27.5 dB were achieved for square shaped DGS and circle shape DG . Three designs which were Design A, Design B and Design C were designed to select the best design for prototyping purpose. Design C offered the best PIN diode isolation performance where high isolation of -35.6 dB and -39.4 dB were achieved using square shaped DGS and circle shape DGS at 1.6 GHz. By fabricating the Design C using FR4 substrate in measurement activity, the measured results clearly showed that the isolation of the series discrete PIN diode was improved using the circle and square shaped DGSs for -27.7 dB and -32.2 dB at frequency of 1.4 GHz and 1.3 GHz. Thus, it was validated that the mathematical modeling had a strong agreement with simulation and measurement results which proved that DGS was capable of improving the isolation performance of discrete PIN diode.